Speckle Interferometric Observations With the Gemini 8-m Telescopes: Signal-to-Noise Calculations and Observational Results - Howell, Steve B.; Furlan, Elise (Frontiers in Astronomy and Space Sciences, 2022)
Using three years of observations with the Zorro and 'Alopeke speckle interferometric instruments at Gemini South and North, respectively, we present an analysis of the sensitivity of the data taken in two narrow-band optical filters centered at 562 and 832 nm. We focus in this paper on model calculations of the predicted signal-to-noise values achievable and the results of over 2500 actual observations. We find that S/N values of several 100 are easily achieved, but that the sky background during full moon is a very limiting factor in the observations, especially those performed in the short wavelength optical spectral range ($<$600 nm) and for targets fainter than $R\sim$14. A comparison of our Gemini speckle observations over six observing semesters reveals that red band-pass observations provide more robust results in general, likely due to better atmospheric performance red-ward of 700 nm. Using the identical instruments on Gemini North and South, we find that similar results are obtained yielding typical contrast limits of 5-9 magnitudes from the diffraction limit out to 1.2 arcsec for a range of target brightness ($V\sim R=3$ to $>16$). Using our S/N model along with the observational results, an estimation of the contrast limits achievable for a given observation can be predicted based on the target brightness, sky illumination and seeing conditions, and the total integration time.